?DISTRIBUTION OF FATTY ACIDS IN THE TRlGLYCERIDES OF CITRULLUS VULGARIS (Biological Sciences - PJSIR, 1998)
The triglycerides separated from Citrullus vulgaris seed oil were fractionated by silver nitrate impregnated thin layer chromatography into six fractions with respect to their degree of unsaturation, The composition and nature of the fatty acids at their 0